Mengelola Hidup Bahagia bagi Mahasiswa: Managing Happy Life for Students - Rianto, Puji; Nashori, Fuad (PengabdianMu: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2024)
Today, many young people are less able to manage their lives to are unhappy, such as insomnia, anxiety, stress, depression, addiction to drugs or alcohol, and problematic emotional relationships. This problem is becoming more severe due to the widespread use of social media. Although social media provides easy and inexpensive communication facilities, it also creates vulnerability for young people due to the flood of communications and hoaxes. This situation is unfavorable for young people, so it needs "treatment." The goal is that students can manage their lives to become happy and have a bright future. The method used is lectures and online discussions. The meeting was held for eight meetings. Through a series of webinars in eight meetings, the activities greatly benefited students. Through these activities, students can learn how to manage their lives and also social media for their lives.